Cash Waqf: A Literature Study Using the Systematic Literature Review (SLR) and Bibliography Methods - Oktavia, Nursyam; Nurwahidin; Hannase, Mulawarman; Nafis, Muhammad Cholil; Fatwa, Nur; Muttaqin, Mohammad Izdiyan (International Journal of Integrative Sciences, 2024)
To analyze cash waqf as a preference for waqf by utilizing systematic literature review (SLR) and bibliometric analysis to identify and synthesize relevant articles from published national and international journals. Using an integrated analysis of Systematic Literature Review (SLR) and Bibliometric methods on 1,109 journal articles indexed in the Scopus database. The PRISMA protocol yielded 60 research articles eligible for review and synthesis related to cash waqf, with saturation achieved through 10 articles. Cash waqf can be an effective tool in driving economic growth. The publication and citation performance over the past ten years of observation is relatively high, with an average citation "h" index between 4 and 42 citations. Seven prominent clusters were identified: Islamic Social Finance and Cash Waqf Institutions, Cash Waqf Development, Cash Waqf Management, the function of Cash Waqf as a tool for improving community welfare, the government's role in supporting cash waqf management, the historical development of waqf along with Islamic financial institutions, and Islamic financial instruments and institutions. This study also reveals gaps in existing research, including the development of innovative cash waqf instruments, ethical management controls, broader poverty alleviation strategies, empowering financial markets in cash waqf development, and the utility of cash waqf as Islamic social finance. This study can be recommended as a consideration for the government, waqf management institutions, and other stakeholders in formulating policies and waqf empowerment programs that are more effective through the optimization of cash waqf, including through Sharia banking products linked to cash waqf, as well as innovative and digital cash waqf management. This forms the basis for analyzing waqf development and comparative studies on the effectiveness of cash waqf models